The Use of a PEG/Ascorbate Booster Following Standard Bowel Preparation Improves Visualization for Capsule Endoscopy in a Randomized, Controlled Study - Mascarenhas-Saraiva, Miguel José; Oliveira, Eduardo; Mascarenhas-Saraiva, Miguel Nuno (Turkish Journal of Gastroenterology, 2021)
Background: Background/Aims: The increasing use of capsule endoscopy (CE) to examine the gastrointestinal tract highlights the needto establish intestinal preparations that ensure optimal visualization while maximizing patient adherence. Thus, we assessed whetherbowel preparation involving dietary restriction and a booster regimen produces adequate CE visualization in a real-world clinical setting.Methods: We conducted a randomized, double-blind, prospective study of CE procedures at 2 tertiary-care centers. Patients were allocatedto 3 groups: group 1 followed a clear liquid diet and fasting-based bowel preparation for the exploration (n = 55); group 2 followedthe same procedure as group 1 and then ingested 1 L of a polyethylene glycol (PEG)/ascorbic acid booster solution when the capsulereached the small intestine (n = 55); and group 3 followed the same procedure but ingesting only 0.5 L of the booster solution (n = 56).The quality of visualization and the average gastric, orocecal and small-bowel transit times were evaluated.Results: A total of 166 patients participated in the study. Significantly higher quality of visualization (Park score) was obtained in group3 (2.28 ± 0.59) than in group 1 (1.84 ± 0.54, P < .001), while there were no significant differences in the average gastric (range: 36.58-48.32 min, P = .277), orocecal (range: 322.58-289.45 min, P = .072), and small-bowel transit time (range: 280.71-249.95 min, P = .286)between the 3 groups.Conclusions: Following a clear liquid diet and fasting-based bowel preparation for CE exploration, administering a booster solution ofPEG/ascorbic acid after the capsule had reached the small intestine improves mucosal visualization and cleansing without affectingcapsule transit times.